Lung cancer in Portugal: an epidemiologic analysis of incidence, geographic variability, survival and associated factors as a basis for the implementation of public policies - Guerreiro, Maria Teresa Dias (2023)
ABSTRACT - Objective: To investigate lung cancer (LC) survival in Portugal and the key factors that can contribute to its improvement, and generate evidence to inform future health policies that can lead to better outcomes for patients and for the health system. Methods: Patient-level data from the regional oncologic registries allowed a nationwide coverage. Background context for LC burden, classification, risk factors, survival, treatment, early diagnosis and quality-of-life was provided. We characterized patients diagnosed with lung cancer, analyzed incidence rates (IR), spatial patterns, and conducted 5-year survival analysis addressing factors as sex, age, histology, stage, treatment and quality-of-care indicators. Finally, we carried-out an overview on current LC screening programs. Results: Male:female ratio 3:1. IR markedly increased with age. Most patients (>80%) had locally-advanced or metastatic disease. Highest IR found in Azores. Most relevant high incidence clusters in Oporto and Lisbon areas. Median overall survival (OS) in a 5-year follow-up study was 264 days and cumulative OS 13.6%. Male gender, increasing age>50, and stage identified as main predictors of decreased survival. Stage had the worst impact. Treatment rate decreased with increasing stage, particularly for surgery (75.2% stage I; 7.8% stage IV) highlighting early diagnosis importance for potentially curative treatment. Treatment showed protective effect on survival but timely treatment did not, likely due to confounding by severity. Evidence supports LC screening implementation targeting high-risk patients to improve outcomes. Conclusions: Our research contributed to identify critical incidence areas. LC survival is highly dependent on early diagnosis, adequate and timely treatment. A targeted LC screening program can potentially transform disease survival.